Structural damage identification through sensitivity-based finite element model updating and wavelet packet transform component energy. (October 2021) - Razavi, Mojtaba; Hadidi, Ali
Abstract: Civil infrastructures deteriorate due to aging, adverse environmental conditions, and inadequate maintenance. Thus, to ensure both safety and serviceability of the structures as well as to mitigate economic losses, it is essential to employ a comprehensive structural health monitoring (SHM) system and appropriate damage identification procedure. Finite element (FE) model updating is one of the most common approaches of damage detection in civil engineering. The most widely used techniques for FE model updating have been developed based on data in the time, time–frequency, and modal domains. In this study, a novel damage identification technique is proposed based on wavelet packet transform component energy (WPTCE). The discrepancy between WPTCE of intact and damaged states of the structure was considered as a residual in the sensitivity-based FE model updating procedure. Two numerical examples, namely a two-dimensional truss bridge and a double layer diamatic dome was used to illustrate the efficiency and applicability of the proposed method in structural damage identification. Sensitivity analysis showed that the WPTCE is a highly sensitive response to structural damages. Further, the results revealed that the proposed method leads to accurate detection of damage, though the measured signals are contaminated by noise.